Towards Enhanced E-Learning Within MOOCs: Exploring the Capabilities of Generative Artificial Intelligence - Harr, Michael Dominic; Wienand, Mareen; Schütte, Reinhard (Proceedings of the Pacific-Asia Conference on Information Systems, 2024)
Massive open online courses (MOOCs) have significantly transformed e-learning by providing global accessibility, collaborative learning opportunities, and high-quality educational content. However, MOOCs face limitations such as limited social interaction, delayed feedback, and linguistic barriers. To overcome these challenges, there is a growing interest in research to leverage artificial intelligence (AI) technologies. In this study, we conduct a systematic literature review examining the capabilities of generative AI (GenAI) and its implications for e-learning in MOOCs. We identify ten capabilities of GenAI, including analytical processing, generative, (personalized) assistant, support, feedback, assessment, communication, reflection, adaptivity, and accessibility. The findings highlight GenAI’s potential to overcome challenges in MOOCs by providing insightful and contextually relevant responses, generating new content, facilitating multilingual interactions, and enhancing the overall e-learning experience. We therefore contribute to the broader understanding of GenAI’s impact on e-learning and suggest avenues for future research on GenAI and its integration in MOOCs.
Keywords: E-Learning; Massive Open Online Courses; Generative Artificial Intelligence; Capabilities